2019
DOI: 10.1111/joop.12285
|View full text |Cite
|
Sign up to set email alerts
|

Pathways through organizational socialization: A longitudinal qualitative study based on the psychological contract

Abstract: In this study, we explore different pathways during organizational socialization through the lens of the psychological contract using in‐depth longitudinal qualitative methods. Analysis of 112 critical incident interviews with 27 newcomers across their first year of work reveals five distinct psychological contract pathways through socialization, within which fulfilment and breach influence adjustment by facilitating or restricting opportunities to learn and integrate, as well as influencing attitudes and beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 67 publications
4
46
0
1
Order By: Relevance
“…Thus, an initial PC state is formed in these newbies’ minds, which acts as a guiding light and base for their future perceptions (Rousseau, 2001). These initial PCs may remain stable until the maintenance phase stage is reached while accumulating more verbal and non-verbal promises in the process (Rousseau et al, 2018; Woodrow & Guest, 2020). Boswell et al (2005) observed that this initial socialisation period (akin to a honeymoon period) into the organisation might spike job satisfaction for employees, especially those keen to learn on the job.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, an initial PC state is formed in these newbies’ minds, which acts as a guiding light and base for their future perceptions (Rousseau, 2001). These initial PCs may remain stable until the maintenance phase stage is reached while accumulating more verbal and non-verbal promises in the process (Rousseau et al, 2018; Woodrow & Guest, 2020). Boswell et al (2005) observed that this initial socialisation period (akin to a honeymoon period) into the organisation might spike job satisfaction for employees, especially those keen to learn on the job.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These reality checks can affect their PCs and can further drive them to seek relevant information checks to measure the discrepancies in their obligated versus delivered inducements in an objective manner (Holtom et al, 2017). As the lack of normative embeddedness of the gig economy starts impacting the workers (Wood et al, 2019), little has been explored on how the employee reactions and the adjustments (or end states of their PCs) shape in response to these adverse shocks (Woodrow & Guest, 2020), especially in the context our study. Though studies have shown that initial PC judgments could determine employee attitudes to a large extent within the first two months of their employment (Delobbe et al, 2016), the intensity and importance of the breach event/violations could still shape the employee coping responses at later stages.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a range of research focusing on the relationship between organisational socialisation and the shaping or fulfillment of psychological contracts (e.g. DeBode et al, 2017;Thomas & Anderson, 1998;Woodrow & Guest, 2020). In this paper, I specifically focus on the tensions between recruitment communication and initial psychological contracts in start-ups.…”
Section: The Intersection Of Recruitment Communication Organisationamentioning
confidence: 99%